Tecnologia e intervenção precoce: produção de vídeos para o apoio às práticas centradas na família no Brasil - Silva, Camila Larissa Vaz (Universidade Federal de São Carlos, 2024)
The present study aimed at the technological production of audiovisual materials (videos) based on the Practical Guides for the Family from the Early Childhood Technical Assistance Center, for submission to its website and also for availability for use in early intervention services in Brazil. Considering the recognition of childhood as a period of greater neural plasticity and acquisition of important skills for later stages of people's lives, the process of early intervention is necessary to provide better development for children who are or may be at risk of developmental delays. Recognizing the importance of the family in the process of child development, Family-Centered Practices are considered more potent, as they view the family as an active member of the team, involving them in the process. Thinking about Family-Centered Practices in early intervention services, a set of guides and checklists were developed at the Early Childhood Technical Assistance Center at the University of North Carolina - Chapel Hill, based on evidence, to guide professionals and families on recommended practices and expected outcomes. These lists and guides are available on the Early Childhood Technical Assistance Center website in areas recognized by the Division of Early Childhood, where the Practical Guides for the Family include explanatory videos about their use. Assuming that Family-Centered Practices are not yet well disseminated in Brazil, the materials were translated into Portuguese (Brazil), aiming to integrate the country into this more current context of early intervention. However, considering that videos are an important tool for understanding for families and early intervention professionals, there was also a need to bring them into the Brazilian context and language, contributing to the dissemination of such practices in Brazil. Therefore, this work aimed to contribute to the advancement of Family-Centered Practices in early intervention services in Brazil, offering its products as a means for professional practice. It is a study of translation and adaptation of audiovisual materials, developed based on the survey of guides and videos that align with the objectives, followed by the translation and production of new videos with audiovisual materials provided by early intervention services that meet the requirements of this work and agree to participate. As a result, more than 90% of the foreign audiovisual material was adapted, which is considered a satisfactory outcome considering the objective of this study.
Technology and early intervention: producing videos to support family-centered practices in Brazil
Keywords: Intervenção precoce; Família; Desenvolvimento infantil; Early intervention; Family; Child development; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL